PENGEMBANGAN MINAT DAN KEMAMPUAN LITERASI AWAL ANAK PRASEKOLAH DI RUMAH - Lisnawati Ruhaena; Juni Ambarwati (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2015)
Early literacy skill of preschool children is very important for children achievement and needsto be stimulated efectively. Parent, especially mother, is a significant person for preschoolchildren. Therefore, how mother stimulate their preschool children to develop early literacyskill still unclear. This study aimed to understand and describe the way of early literacydevelopment at home in family context.  Data was collected by interview and observation toobtain information about the way mother stimulated children interest and skill of early literacy.The informan were six mothers who had 4-6 years old preschool children. Content analyzedshowed that early literacy stimulation had been done using story books and multimediatechnology such as televition and computer. Mother were involved in early literacy activities,however the mother-child interaction were much more directive rather than facilitative.Literacy activities tent to be formal instruction and learning process so that children lessinterest and became unmotivated. Children had less chance to actively explore and manipulateobjects in constructing their knowledge and understanding. Mother did not apply constructivisttheory yet. Recommendation for solving the problem and further study is discussed.   Key words: interest, skill, early literacy, preschool.